(3Gdbhd GdcGTa Yf CMcGe GdGSJHGfg aj GdhXGFas - (3eMeO Hf CMeO Hf GdeSfGhj Hf eMeO Hf CHj HcQ, CHh YHO Gddg GdOdGFj,J (B1136 (3g` s ((3CHh GdVjGA CMeO Hf EHQGgje HGNQe GdEOQjSi s)
(3ChdgG (B:s
(3hHYO agPG JbjjO cGTa Yf CMcGe GdESJfGHI ai GdhXGFa s
(3BNQgG (B:s
(3hGdMeO ddg Ydi eG CfYe hYde ef TQGFY Ojfg eG de JYde hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjeG s
(3GdfSNI HgG MhGTs
(3YdjgG NW GdeDda ai YOI ehGVYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B259s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(194D) s
Keywords: (3Gdabg GdeGdcjs